Portable water sprinkler / Muhammad Amiruddin Anuar & Aminuddin Roslan - Anuar, Muhammad Amiruddin; Roslan, Aminuddin (2015)
The Portable Water Sprinkler System is used to automatically watering plant. This project is based on microcontroller and sensor operation. The microcontroller used is ATMEGA 328P that attach to Arduino board and the sensor used is a soil moisture sensor. The sensor detects the moisture content of the soil and sent the signal required to Arduino board. If the moisture content of the soil value is lower than the trigger value, the pump will be triggered for sprinkling process. Otherwise, the pump will not be triggered. Then the water tank used to store the water and connect it to water pump. Water- level indicator also provided to detect the level of water in the tank. When water in the tank is full, green LED will light up. When water at half full, yellow LED will light up. Red LED will light up when water level in the tank about to empty or low. This Portable Water Sprinkler System will helps for those who got small garden in their housing area. Their plants will not be dry if no rain when they going out to somewhere else in few days. Users can have different size of the water tank according to their convenient. The bigger the water tank, the longer the systems can be operated and users will not worried about their lovely plants